Chapter Ricerche sullo Zibaldone Magliabechiano: il De doctoribus seu inventoribus tra Paolino Veneto e Boccaccio - Mariotti, Damiano (Studi e saggi, 2022)
In the De doctoribus seu inventoribus inserted in the Zibaldone Magliabechiano, Boccaccio reports names and short biographies of several distinguished men and women that he read in Paolino Veneto's Chronologia Magna. By comparing this list with its original source, the article means to reconstruct the modus operandi of the Certaldese during the study for the production of his erudite works of the late age, highlighting the importance of such a tool for understanding the intellectual baggage of its author and his methods of reworking the material.